A critical appraisal of ferroptosis in Alzheimer’s and Parkinson’s disease: new insights into emerging mechanisms and therapeutic targets - Soni, Priyanka; Ammal Kaidery, Navneet; Sharma, Sudarshana M.; Gazaryan, Irina; Nikulin, Sergey V.; Hushpulian, Dmitry M.; Thomas, Bobby (Frontiers in Pharmacology, 2024)
Neurodegenerative diseases represent a pressing global health challenge, and the identification of novel mechanisms underlying their pathogenesis is of utmost importance. Ferroptosis, a non-apoptotic form of regulated cell death characterized by iron-dependent lipid peroxidation, has emerged as a pivotal player in the pathogenesis of neurodegenerative diseases. This review delves into the discovery of ferroptosis, the critical players involved, and their intricate role in the underlying mechanisms of neurodegeneration, with an emphasis on Alzheimer's and Parkinson's diseases. We critically appraise unsolved mechanistic links involved in the initiation and propagation of ferroptosis, such as a signaling cascade resulting in the de-repression of lipoxygenase translation and the role played by mitochondrial voltagedependent anionic channels in iron homeostasis. Particular attention is given to the dual role of heme oxygenase in ferroptosis, which may be linked to the non-specific activity of P450 reductase in the endoplasmic reticulum. Despite the limited knowledge of ferroptosis initiation and progression in neurodegeneration, Nrf2/Bach1 target genes have emerged as crucial defenders in anti-ferroptotic pathways. The activation of Nrf2 and the inhibition of Bach1 can counteract ferroptosis and present a promising avenue for future therapeutic interventions targeting ferroptosis in neurodegenerative diseases.